Quality Assurance in Private Higher Education Institutions in Ghana: Practices and Challenges - Grace Ahenkan Arthur; Alfred Kuranchie (Social Education Research, 2022)
The study sought to unveil how private universities approach Quality Assurance (QA) practices (both internal and external QA practices) in order to achieve their institutional goals. To achieve this purpose, a qualitative approach was followed. The study employed phenomenology as a design to explore the views of key informants who were purposefully selected from the institutions. The key officers served as study participants due to their positions and functions which are directly related to QA issues and practices in the institutions. They were information-rich in the subject of the study. Face-to-face interviews were conducted to generate data to answer the research questions. The study revealed that private universities adhere to the regulators' guidelines and directives in the execution of their responsibilities. Both internal and external practices are in line, hook and sinker manner with best practices although they faced some challenges in their bid to ensure quality in both administrative and academic functions of the universities. It is imperative, therefore, for some of the private universities to give priority to resourcing their QA units with well-equipped human and material resources in order to achieve their institutional goals.